Markers of Myocardial Ischemia in Patients with Obstructive Sleep Apnea and Coronary Artery Disease. (18th May 2015) - Valo, Misa; Wons, Annette; Moeller, Albert; Teupe, Claudius
Abstract : Obstructive sleep apnea (OSA) is characterized by intermittent hypoxia during sleep. We tested the hypothesis that nocturnal myocardial ischemia is detectable by ST segment depression and elevation of high sensitive troponin T (hsTrop T) and B-type natriuretic peptide (NT-proBNP) in patients with OSA and coexisting coronary artery disease (CAD). Twenty-one patients with OSA and CAD and 20 patients with OSA alone underwent in-hospital polysomnography. Blood samples for hsTrop T and NT-proBNP measurements were drawn before and after sleep. ST segment depression was measured at the time of maximum oxygen desaturation during sleep. The apnea-hypopnea-index (AHI), oxygen saturation nadir, and time in bed with oxygen saturation of ≤80% were similar in both groups. Levels of hsTrop T and NT-proBNP did not differ significantly before and after sleep but NT-proBNP levels were significantly higher in patients suffering from OSA and CAD compared to patients with OSA alone. No significant ST depression was found at the time of oxygen saturation nadir in either group. Despite the fact that patients with untreated OSA and coexisting CAD experienced severe nocturnal hypoxemia, we were unable to detect myocardial ischemia or myocyte necrosis based on significant ST segment depression or elevation of hsTrop T and NT-proBNP, respectively.